Smokeless Tobacco (SLT) Consumption Behavior and Associated Socio-Demographic Factors Among Bangladeshi Dental Patients - Syed Billal Hossain; Tabassum Ferdous; Md. Hazrat Ali; Md. Nawal Sarwer; Akibul Islam Chowdhury; Mir Apel Mahmud; Lipi Rani Mondal; Nasima Akter Mukta (Tobacco Use Insights)
Introduction: Oral consumption of smokeless tobacco (SLT) is associated with poor periodontal health and a range of oral diseases, some of which are malignant or potentially malignant. This research aims to ascertain whether a certain socio-demographic category of individuals with any type of oral syndrome has a higher likelihood of using and consuming smokeless tobacco in specific ways. Method: A tertiary dental institution in Dhaka conducted cross-sectional research on adult oral hygiene patients from April 2024 to September 2024. A semi-structured questionnaire was replied by 156 research participants. Purposive sampling was used to choose study participants who were at least 18 years old, SLT users, and had at least ten natural teeth. Results: There might not be any gender disparity in the SLT intake because this study was conducted at the outdoor department of a tertiary dental facility with patients from a range of socio-demographic backgrounds. All the socio-demographic variables, including age, gender, marital status, number of children, family size, and employment, found to be significantly ( P ≤ 0.05) associated with consumption of SLT along with smoking. Living location and education were the only exceptions. However, the length of time a person has consumed smokeless tobacco is affected by his/her socio-demographic factors such as age, residence region, marital status, number of family members, and number of children substantially ( P ≤ 0.05). Conclusion: A coordinated and collaborative initiatives aimed at reducing smokeless tobacco consumption and smoking is required to prevent dental health degradation, especially among the vulnerable groups (eg, women, the elderly, residents of rural areas).